Same Semantics of the Signal - What Do We Cluster with what Representation - Barnhill, Alexander; Traub, Oliver; Nöth, Elmar; Maier, Andreas; Bergler, Christian (Proceedings of the International Conference on Acoustics, Speech, and Signal Processing, 2025)
Semantic clustering of bioacoustic signals is crucial for a deeper understanding of intra-class differences. This is particularly important for understanding killer whale signals, as their vocalizations are learned behaviors and determination of matrilineal-specific dialects is reliant upon subtle differences within instances which may be characterized into a single larger category. Aspects of data collection may have an effect on how these calls are grouped, and it is therefore necessary to understand what the focus of the feature generation algorithm is. This study addresses the impact of factors such as recording conditions and environment, together with its respective relative noise levels, by first analyzing two different deep learningand data-driven feature representations, either derived by an undercomplete autoencoder or a supervised call type classifier. These are then compared with representations generated by two state-of-the-art transformer-based tools, namely HuBERT and Wav2Vec
Keywords: Killer whale; bioacoustics; semantics; clustering